2021
DOI: 10.21203/rs.3.rs-1110536/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Heat Is on: a Simple Method to Increase Genome Editing Efficiency in Plants

Abstract: Background: Precision genome mutagenesis using CRISPR/Cas has become the standard method to generate mutant plant lines. Several improvements have been made to increase mutagenesis efficiency, either through vector optimisation or the application of heat stress. Results: Here, we present a simplified heat stress assay that can be completed in six days using commonly-available laboratory equipment. We show that three heat shocks (3xHS) efficiently increases indel efficiency of LbCas12a and Cas9, irrespective of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(20 citation statements)
references
References 41 publications
(83 reference statements)
0
20
0
Order By: Relevance
“…To this end, we crossed the p34 iCRISPR -1 mutant with pAP2S:AP2S-GFP/ap2s , pAP3B:AP3B-GFP/pat2-1 , and pAP4M:AP4M-GFP/ap4m and used the p35S-GFP /Col-0 plants as control. F2 seeds carrying the CRISRP/Cas9 construct were selected by seed fluorescence 49 and used for further experiments. Immunoblot analysis indicated that the levels of AP2S-GFP and AP4M-GFP, but not of AP3B-GFP and GFP, were reduced after β-estradiol induction (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, we crossed the p34 iCRISPR -1 mutant with pAP2S:AP2S-GFP/ap2s , pAP3B:AP3B-GFP/pat2-1 , and pAP4M:AP4M-GFP/ap4m and used the p35S-GFP /Col-0 plants as control. F2 seeds carrying the CRISRP/Cas9 construct were selected by seed fluorescence 49 and used for further experiments. Immunoblot analysis indicated that the levels of AP2S-GFP and AP4M-GFP, but not of AP3B-GFP and GFP, were reduced after β-estradiol induction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 and Supplemental Data 1) and all three AP-5 subunits were identified together with the thus far uncharacterized proteins in plants ZINC FINGER FYVE DOMAIN-CONTAINING PROTEIN (ZFYVE) (AT2G25730) and SPATACSIN CARBOXY-TERMINUS PROTEIN (AT4G39420). Further sequence alignments revealed the homology of the SPATACSIN CARBOXY-TERMINUS PROTEIN and the ZFYVE protein to the mammalian SPG11 (with 60% similarity and 22.83% identity) and SPG15 (with 49% similarity and 22.57 identity) proteins, respectively, the two known accessory proteins of the AP-5 complex in mammalian cells 2, 49 . Consistent with the AP-3 and AP-4 interactome analyses, AP5M co-purified with four AP-4 subunits (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the white spots or mosaic sectors on leaves of phytoene desaturase3 ( pds3 ; AT4G14210 ) plants are difficult to observe and easily obscured by faster‐growing plants. These issues prompted us to develop an alternative, low‐tech methodology that allows for a straightforward induction of heat stress in plants grown on sterile media (Blomme et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In this methodology article, we present a detailed description of our simple and straightforward setup to impose heat stress on Arabidopsis and tobacco using commonly available laboratory equipment (Basic Protocol 1; Blomme et al., 2022). Our simplified three heat shock (3×HS) protocol allows researchers to increase genome editing efficiencies in the T1 generation by 15%‐66%, depending on the target site, for many CRISPR applications.…”
Section: Introductionmentioning
confidence: 99%